Combating spyware in the enterprise - Baskin, Brian; Piltzecker, Tony, 1975- (Rockland, MA : Syngress, 2006)
Provides information on defending enterprise networks from sophisticated and malicious spyware. This book begins by examining the various types of insidious spyware and adware that propagate across the internet and infiltrate enterprise networks. It also aims to uncover spywares' intricate economy and network of malicious hackers and criminals.
An overview of spyware -- The transformation of spyware -- Spyware and the enterprise network -- Real spyware : crime, economic espionage, and espionage -- Solutions for the end user -- Forensic detection and removal -- Dealing with spyware in a non-Microsoft world -- The frugal engineer's guide to spyware prevention.
Includes index.
Keywords: Computer security; Spyware (Computer software); Electronic books